Board Game in Speaking Skill - Cut Ratna Putri; Bustami Usman; Chairina Nasir (Research in English and Education Journal, 2017)
This quantitative study is about Board Game to develop students’ speaking skill on expressing their ideas on descriptive text especifically on describing people.  The speaking tests were used as the instrument, which are divided into pretest and post-test.   A number of 25 students of SMPN 11 Banda Aceh participated in this study that chosen randomly from eight grader. The scores were tabulated statistically by using t-test.  The result showed the hypothesis testing of the students’ pronunciation performance is significantly improved (19.7 t-count 1.71 t-table).  It was found that this technique improved students’ speaking skill in the target language and their acuracy.  It also could give positive reinforcement on fluency vocabulary and accuracy while learning within this technique. The finding suggested to use Board Game as a technique in improving speaking skill.  The study has demonstrated that the treatment activities have improved the students’ interest to speak the target language.